Evaluasi dan Antisipasi Kebijakan Penanggulangan Kelangkaan BBM - Wirijadinata, Jat Jat (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2006)
The problem of proverty and energy crisis has created the withdrawl oil energy subsidies policy, and resulted the unintended policy impact, such as the deterioration of economic life of the people, the destruction of public investment climate and demoralitation. Nowadays the government has issued the bio energy alternatives policy. The question is, how the seriousity of the government to implement this policy? How far the proffesionality of the policy actors, all are depend on most of the policy system.